2019
DOI: 10.1371/journal.pone.0217875
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of abnormal QRS peaks predicts response to cardiac resynchronization therapy and tracks structural remodeling

Abstract: Background Although QRS duration (QRSd) is an important determinant of cardiac resynchronization therapy (CRT) response, non-responder rates remain high. QRS fragmentation can also reflect electrical dyssynchrony. We hypothesized that quantification of abnormal QRS peaks (QRSp) would predict CRT response. Methods Forty-seven CRT patients (left ventricular ejection fraction = 23±7%) were prospectively studied. Digital 12-lead ECGs were recorded during native rhythm at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Patients having QRS complexes > 150 ms and echocardiographic indications of mechanical dyssynchrony after 6 months who had implantation of Cardiac Resynchronization Therapy show a large decrease in LV diameter (LVEDD, LVESD) and a significant improvement in MPI [8][9][10]. There is a failure rate of over 30% with CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Patients having QRS complexes > 150 ms and echocardiographic indications of mechanical dyssynchrony after 6 months who had implantation of Cardiac Resynchronization Therapy show a large decrease in LV diameter (LVEDD, LVESD) and a significant improvement in MPI [8][9][10]. There is a failure rate of over 30% with CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Major morphological changes in native QRS or complete resolution of LBBB after CRT are rarely observed and occurred only in few cases in the included studies [13,26]. Although, minor morphological changes may occur, as described by Suszko et al [23]. They assessed the number of leads with fragmented QRS before CRT and during followup with high resolution ECG and found that that reduction of leads with fragmented QRS was strongly associated with mechanical response.…”
Section: Mechanism Of Reverse Electrical Remodelingmentioning
confidence: 91%
“…In addition, we compared extent of iQRS duration change in patients with mechanical response versus without mechanical response. Data were extracted from six studies with 356 participants, of whom 231 (64.9%) were defined as mechanical responders [14,19,[21][22][23][24]. We found that while mechanical responders had a mean of iQRS shortening of 7.7 ms, mechanical non-responders experienced widening of iQRS by mean of 5.2 ms (Supplementary Fig.…”
Section: Association Between Electrical and Mechanical Responsementioning
confidence: 99%
“…The evaluation of electrical dyssynchrony using QRS duration (QRSd) was more reliable to predict CRT outcome [4]. Nonetheless, in patients with QRSd < 150 ms, there are limited data on markers of electrical dyssynchrony [5]. Hence, recognition of patients who are likely to benefit from CRT before the device implantation is still challenging.…”
Section: Introductionmentioning
confidence: 99%